Do GST polymorphisms influence in the pathogenesis of diabetic nephropathy?. (15th December 2018) - de Lima, Rayane Mendes; dos Anjos, Laura Raniere Borges; Alves, Thales Biffe; Coelho, Alexandre Siqueira Guedes; Pedrino, Gustavo Rodrigues; da Silva Santos, Rodrigo; da Silva Cruz, Aline Helena; da Silva Reis, Angela Adamski
Abstract: Diabetic patients often develop Diabetic Nephropathy (DN) despite severe long-lasting hyperglycemia, while others develop DN even under intensive insulin therapy. This indicates that factors other than chronic hyperglycemia may also contribute to the susceptibility to the development of DN. The purpose of this case-control study was to investigate the possible role of GSTM1 and GSTT1 deletion polymorphisms, and Single Nucleotide Polymorphism (SNP), GSTP1 313 A > G (Ile105Val), in DN susceptibility. Multiple logistic regression analysis revealed that the occurrence of GST polymorphisms in the Central Brazilian population was not associated with increased risk of DN. However, the presence GSTT1 null genotype suggest an increase trend in systolic blood pressure and opposite inference was observed for the GSTP1 genotype (Ile⁄Val or Val⁄Val). On the order hand, other studies may clarify the relationship of these polymorphisms with DN and help in the prevention of this disease. Highlights: The hypothesis of triple or double interaction between the genotypes GSTM1, GSTT1 and GSTP1 demonstrated there is no association for pathogenesis of Diabetic Nephropathy. The null genotypes GSTM1, GSTT1 and GSTP1 did not reveal an increase in risk of occurrence for DN. The presence GSTT1 null genotype suggest an increase trend in systolic blood pressure and an opposite inference was observed for the GSTP1 genotype (Ile/Val or Val/Val), which demonstrate a decrease in systolic blood pressure.